An empirical investigation into the firm, country, and patent portfolio-specific characteristics of foreign patent sellers to the Chinese market - Keaveney, cailean (2020)
The purpose of this study is to investigate the firm, country, and patent portfolio-specific characteristics of firms (located outside of China) that sell patents to the Chinese market. Using regression analysis, this study examines the relationship among a firms’ turnover and size and the total number of patents it sells to the Chinese market. In addition, the extent to which the intellectual property rights and business culture complexity of the seller firms home countries enable or hinder the flow of patents to the Chinese market are considered. Finally, patent portfolio-specific characteristics such as the total number of claims and the total number of forward citations associated with a seller firms patent portfolio are analysed as indicators of value. Turnover was found to have a negative impact on the total number of patents a firm sells to the Chinese market. However, employee count did not have a statistically significant relationship with the total number of patents a firm sells to the Chinese market. Surprisingly, stronger intellectual property rights were found to have a negative impact on the number of patents a firm sells. On the contrary, firms in countries that signal less complex business cultures sell more patents to the Chinese market compared to firms in countries with complex business cultures. Finally, the number of claims and the number of forward citations associated with a seller firms’ patent portfolio were found to have a positive statistically significant impact on the number of patents a firm sells to the Chinese market.